Vernacular deconstruction: undermining spin - Martin, J. R (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper is concerned with the way in which three popular culture texts are deployed to challenge discourse which naturalises war. Each text mobilises ideational resources to draw attention to the material cost of war and interpersonal resources to re-align reader/viewers into peace seeking communities; in addition, each text deploys dramatic shifts in semiosis to re-focus reader/viewers’ understanding and evaluation of armed struggle. The analysis is offered as a contribution to the field of positive discourse analysis and its interpretation of texts which function to make the world a better place.